VNLG-152R and its deuterated analogs potently inhibit/repress triple/quadruple negative breast cancer of diverse racial origins in vitro and in vivo by upregulating E3 Ligase Synoviolin 1 (SYVN1) and inducing proteasomal degradation of MNK1/2 - Thankan, Retheesh S.; Thomas, Elizabeth; Purushottamachar, Puranik; Weber, David J.; Ramamurthy, Vidya P.; Huang, Weiliang; Kane, Maureen A.; Njar, Vincent C. O. (Frontiers in Oncology, 2023)
Triple-negative breast cancer (TNBC) and its recently identified subtype, quadruple negative breast cancer (QNBC), collectively account for approximately 13% of reported breast cancer cases in the United States. These aggressive forms of breast cancer are associated with poor prognoses, limited 2 This is a provisional file, not the final typeset article treatment options, and lower overall survival rates. In previous studies, our research demonstrated that VNLG-152R exhibits inhibitory effects on TNBC cells both in vitro and in vivo and the deuterated analogs were more potent inhibitors of TNBC cells in vitro. Building upon these findings, our current study delves into the molecular mechanisms underlying this inhibitory action. Through transcriptome and proteome analyses, we discovered that VNLG-152R upregulates the expression of E3 ligase Synoviolin 1 (SYVN1), also called 3-hydroxy-3-methylglutaryl reductase degradation (HRD1) in TNBC cells. Moreover, we provide genetic and pharmacological evidence to demonstrate that SYVN1 mediates the ubiquitination and subsequent proteasomal degradation of MNK1/2, the only known kinases responsible for phosphorylating eIF4E. Phosphorylation of eIF4E being a rate-limiting step in the formation of the eIF4F translation initiation complex, the degradation of MNK1/2 by VNLG-152R and its analogs impedes dysregulated translation in TNBC cells, resulting in the inhibition of tumor growth. Importantly, our findings were validated in vivo using TNBC xenograft models derived from MDA-MB-231, MDA-MB-468, and MDA-MB-453 cell lines, representing different racial origins and genetic backgrounds. These xenograft models, which encompass TNBCs with varying androgen receptor (AR) expression levels, were effectively inhibited by oral administration of VNLG-152R and its deuterated analogs in NRG mice. Importantly, in direct comparison, our compounds are more effective than enzalutamide and docetaxel in achieving tumor growth inhibition/repression in the AR+ MDA-MD-453 xenograft model in mice. Collectively, our study sheds light on the involvement of SYVN1 E3 ligase in the VNLG-152R-induced degradation of MNK1/2 and the therapeutic potential of VNLG-152R and its more potent deuterated analogs as promising agents for the treatment of TNBC across diverse patient populations.